Bowel dysfunction in spinal cord injury - Naicker, Amaramalar Selvi; Syed Waseem Ahmad, Sharifah Roohi; Naicker, Manimalar Selvi; O, Zaleha (Malaysian Medical Association, 2008)
Bowel Dysfunction is one of the least looked at problems in Spinal Cord Injury (SCI). The goals of this study are to understand bowel dysfunction in SCI and its effects on quality of life (QOL). Cross-sectional study based on interview and assessment of 41 clients. A majority of them were dissatisfied. Bowel opening time was long in about 65% while 76.6% were incontinent. Socially, approximately half refrained from outings even though 90.3% of them carried out bowel evacuation before going out. Attention to bowel education is necessary to improve social continence.